Influence Of Short Heat Treatment On The Microstructures And Mechanical Properties Of Thixoformed Aluminum Alloy Composite - Salleh, Mohd Shukor; Hashim, Hanizam; Abd Rahman, Ammar; Sulong, Abu Bakar; Abd Rahman, Ammar (Malaysian Tribology Society, 2021)
Typical T6 heat treatment is commonly applied to aluminum alloy to improve mechanical strength and prevent a catastrophic failure. However, previous studies of T6 have not dealt with aluminum alloy reinforced by carbon nanotubes composite in great detail. In addition, the T6 heat treatment is time-consuming and incurred a high operational cost to production. The present study was designed to determine the effect of a short T6 (ST6) on mutiwalled carbon nanotubes (MWCNT)-A356 alloy composite. The ST6 consists of 1 hour-solution treatment (ST), water quenching at room temperature, and 2 hoursartificial aging (AA). The results revealed that a total of ST and AA is enough to dissolve soluble phases and homogenize alloy elements, and MWCNT particles to be distributed uniformly in the matrix. The effectiveness of the ST6 heat treatment was also shown in the overall improvement of the alloy and composite mechanical properties against the standard T6 heat treatment. The highest values of yield strength, ultimate tensile strength, elongation to fracture, and hardness of the composite obtained were 215 MPa, 277 MPa, 6.8%, and 106.4 HV respectively